PENDIDIKAN KESEHATAN KELUARGA DALAM PEMELIHARAAN KESGILUT PADA MASYARAKAT DUSUN PENGGERATAN MUARO JAMBI - Linda Marlia; Yesi Nurmawi; Junaidi Junaidi; Sukarsih Sukarsih (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Abstract Dental and oral health problems in Indonesia tend to increase, namely in 2018 (57.6%) compared to 2013 (25.9%) and 2007 (23.4%), Jambi Province (45%) and Muaro District Jambi (33.96%). The proportion of correct dental behavior in the age group above 3 years in Jambi Province is only 1% and Muaro Jambi Regency (1.16%), the lowest nationally. Marlia and Silfia (2019) that counseling with videos in the Jambi regional language is effective in improving dental skills in Pelempang Village children. As a follow-up, it is hoped that family health education efforts can increase the degree of difficulty in the Dusun Pengeratan community using the Jambi regional language video. This service is carried out using the Community Partnership Program (PKM) method through counseling, demonstrations and assistance to the Dusun Pengeratan community in maintaining health problems. The results of this PKM found that there was an increase in the knowledge and skills of respondents in maintaining mental health problems in Dusun Pengeratan. Keywords: dental and oral health, family health education